Buckland's complete book of witchcraft - Buckland, Raymond (Llewellyn Publications, 2002)
Here is the most complete self-study course in modern Wicca available, written by the person who first went public with "The Old Religion" in the United States. For group or solitary use, it includes rituals; exercises for developing psychic talents; information on all major "sects" of the Craft; sections on tools, beliefs, dreams, meditations, divination, herbal lore, healing, ritual clothing; and much, much more. Even those who have practiced Wicca for years find useful information in "Buckland's Complete Book of Witchcraft," and many covens are using it as their textbook. Profusely illustrated and full of music and chants.